Evolutionary response to coexistence with close relatives: increased resistance against specialist herbivores without cost for climatic‐stress resistance. (7th June 2019) - Pihain, Mickael; Gerhold, Pille; Ducousso, Alexis; Prinzing, Andreas
Abstract: Why can hosts coexist with conspecifics or phylogenetically proximate neighbours despite sharing specialist enemies? Do the hosts evolve increased enemy resistance? If so, does this have costs in terms of climatic‐stress resistance, or in such neighbourhoods, does climatic‐stress select for resistances that are multifunctional against climate and enemies? We studied oak ( Quercus petraea ) descendants from provenances of contrasting phylogenetic neighbourhoods and climates in a 25‐year‐old common garden. We found that descendants from conspecific or phylogenetically proximate neighbourhoods had the toughest leaves and fewest leaf miners, but no reduction in climatic‐stress resistance. Descendants from such neighbourhoods under cold or dry climates had the highest flavonol and anthocyanin levels and the thickest leaves. Overall, populations facing phylogenetically proximate neighbours can rapidly evolve herbivore resistance, without cost to climatic‐stress resistance, but possibly facilitating resistance against cold and drought via multifunctional traits. Microevolution might hence facilitate ecological coexistence of close relatives and thereby macroevolutionary conservatism of niches.